Barbados : 2010 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
The global crisis has hit Barbados front and center. The broad economic weakness has hurt the labor market, while inflation remains stubbornly elevated. The major challenge ahead is to put public debt on a steady declining path to support both domestic and external stability. A decisive fiscal adjustment is the best way to protect the exchange rate peg while the current monetary stance is broadly appropriate. Banks remain healthy, but tighter regulations are needed. Supervision of nonbank financial institutions needs to be revamped.